Rabbinic Authority : the Vision and the Reality. - Warburg, A. Yehuda (Urim Publications, 2013)
Introducing English-speaking readers to the parameters and scope of rabbinic authority in general, and the workings of the institution of the beit din-the Jewish court of law-in particular, this book presents 10 rulings in cases of Jewish civil law that the author handed down as a member of a beit din panel. These decisions touch on matters pertaining to employment termination, tenure rights and severance pay, rabbinic contracts, issues in the not-for-profit boardroom, real estate brokerage commission, drafting a halakhic will, a revocable living trust agreement, the division of marital assets.